KANDUNGAN BAHAN ORGANIK, N-ALKANA, AROMATIK DAN TOTAL HIDROKARBON DALAM SEDIMEN DI PERAIRAN RAHA KABUPATEN MUNA, SULAWESI TENGGARA - Marsaoli, Muhajir (Makara Journal of Science, 2004)
The content of organic material, n-alkana, aromatic compound and hydrocarbon total in the sediment was carried out in the waters of Raha, Southeast of Sulawesi. Investigation on content of organic material, n-alkana, aromatic compound and hydrocarbon total in the sediment was carried out in the waters of Raha, Southeast of Sulawesi in June 2001. The results showed that the sediment at station 1 and 4 were polluted by hydrocarbon compound. This condition is showed by F1/F2 ratio (comparation between saturated hydrocarbon fraction with aromatic hydrocarbons fraction) > 1. According to NAS (National Academy of Science) criteria on total hydrocarbon content, station 2 and 5 only were polluted by hydrocarbons compound (>100 ppm).